2021
DOI: 10.1152/ajpendo.00070.2021
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophage populations and inflammation are associated with systemic inflammation and insulin resistance in obesity

Abstract: Obesity is accompanied by numerous systemic and tissue-specific derangements, including systemic inflammation, insulin resistance, and mitochondrial abnormalities in skeletal muscle. Despite growing recognition that adipose tissue dysfunction plays a role in obesity-related disorders, the relationship between adipose tissue inflammation and other pathological features of obesity is not well-understood. We assessed macrophage populations and measured the expression of inflammatory cytokines in abdominal adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 98 publications
4
59
2
2
Order By: Relevance
“…Although exercise leads to many favorable adaptations and represents an important behavioral strategy to lessen the burden of obesity, the notable variability in exercise responsiveness (10) Gene-centric GSEA identified downregulation of numerous gene sets in individuals with obesity, including "Fatty Acid Metabolism," "Citric Acid Cycle," "Oxidative Phosphorylation," and "Respiratory Electron Transport." These gene sets also emerged as significantly downregulated in muscle in individuals with obesity by global proteomics and they are consistent with literature that has demonstrated that mitochondrial function is impaired with obesity (16) and that it may be linked with insulin resistance (26). Other notably downregulated gene sets were relevant to muscle protein synthesis, including "Translation," "Mitochondrial Protein Import," "Mitochondrial Translation," "Complex I Biogenesis," "Ribosome,"…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although exercise leads to many favorable adaptations and represents an important behavioral strategy to lessen the burden of obesity, the notable variability in exercise responsiveness (10) Gene-centric GSEA identified downregulation of numerous gene sets in individuals with obesity, including "Fatty Acid Metabolism," "Citric Acid Cycle," "Oxidative Phosphorylation," and "Respiratory Electron Transport." These gene sets also emerged as significantly downregulated in muscle in individuals with obesity by global proteomics and they are consistent with literature that has demonstrated that mitochondrial function is impaired with obesity (16) and that it may be linked with insulin resistance (26). Other notably downregulated gene sets were relevant to muscle protein synthesis, including "Translation," "Mitochondrial Protein Import," "Mitochondrial Translation," "Complex I Biogenesis," "Ribosome,"…”
Section: Discussionsupporting
confidence: 84%
“…A muscle biopsy was performed on the exercised leg 3.5 hours following completion of the exercise bout. The 2‐day inpatient period, with resting and postexercise biopsies performed on separate days, was required to accommodate the additional outcomes pertinent to the aims of the parent project, some of which have been published previously (16) and others which are ongoing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that adipose tissue-derived exosomes not only function in paracrine and endocrine modes, but also act as intercellular communicators to facilitate the transition of adipocytes towards maturity ( 43 ). In studies of the role of exosomes in systemic metabolism, adipocyte-derived exosomes were found to be mediators linking obesity and insulin resistance in surrounding tissues such as the liver, interacting with adjacent sites to promote lipid esterification ( 44 , 45 ). Connolly et al.…”
Section: Role Of Adipose Tissue-derived Exosomes In Metabolic Diseasesmentioning
confidence: 99%
“…Then the increase of free fatty acids in adipose tissue causes the release of reactive oxygen species, which in turn causes oxidative stress or hypoxia in tissues, and finally makes the body present a state of systemic low-grade inflammation. 3,4 Inflammatory factors reduce the insulin sensitivity of muscle, fat and other tissues by affecting the insulin signaling pathway, thus causing IR. 5 For example, TNF-α could inhibit tyrosine phosphorylation of insulin receptor substrate-1 (IRS-1) through activating the ERK and JNK inflammatory pathways, resulting in the inhibition of glucose uptake.…”
Section: Introductionmentioning
confidence: 99%